Internal construct validity of the Brazilian version of a tool for assessing the population's knowledge of human papillomavirus - Fabiana Schuelter Trevisol; Rodrigo Dias Nunes; Gabriel Oscar Cremona Parma; André Luciano Manoel; Clávison Martinelli Zapelini; Daisson José Trevisol; Jefferson Traebert
ABSTRACT: Objective: To verify the internal construct validity of the Brazilian Portuguese version of a tool for measuring the general population's knowledge of human papillomavirus (HPV). Materials and methods: A cross-culturally adapted Brazilian Portuguese version of a measurement tool originally designed for English speaking populations was administered to 330 adults in Tubarão, Santa Catarina, Southern Brazil. After examining the overall suitability of the method, we performed investigations based on the item response theory and exploratory factor analysis. Results: Ten of the 29 items presented a low contribution to the construct and were excluded from subsequent analysis. The factor analysis yielded three factors, which explained approximately 51% of the variance variability. A different arrangement from the original measurement tool was found: general HPV knowledge, with six items; HPV vaccination knowledge, with five items; HPV transmission and testing knowledge, with eight items. Conclusion: The Brazilian Portuguese version under study presented a different behavior from the original measurement tool, but proved to be a reliable and valid instrument in assessing the Brazilian population's knowledge about HPV.